Ultrastructural study of Mycoplasma pneumoniae in organ culture. - Wilson, M H (1976)
The ultrastructure of Mycoplasma pneumoniae M129 was studied by using specialized staining methods for thin-section transmission electron microscopy. Nucleic acid was shown in the cytoplasmic granules and fibrillar material in the nuclear region. The central filament of the highly structured tip contained basic protein. With one method of fixation, parallel filaments were seen in the central core. M. pneumoniae was enveloped in an extracellular mucoprotein layer that was especially concentrated around its terminal structure.